Patient and physiotherapist perceptions of the Getting Recovery Right After Neck Dissection (GRRAND) rehabilitation intervention: a qualitative interview study embedded within a feasibility trial. Issue 11 (14th November 2022) - Fordham, Beth; Smith, Toby O; Lamb, Sarah; Morris, Alana; Winter, Stuart C
Abstract : Objective: The Getting Recovery Right After Neck Dissection (GRRAND) intervention is a physiotherapy programme for patients with head and neck cancer who have undergone neck dissection. The aim of this qualitative study was to understand if the intervention was useful, acceptable and whether it was feasible to conduct a randomised controlled trial (RCT). Design: This qualitative study was embedded within the GRRAND-Feasibility (GRRAND-F) Study. Setting: Participants were recruited from four acute National Health Service hospitals in England between 2020 and 2021. Participants: We interviewed four usual care and four intervention patient-participants from a single study site (Oxford). Six were male, two were female. All were white British ethnicity. We interviewed two physiotherapists from Oxford who delivered the GRRAND-F intervention, and physiotherapists from Birmingham, Poole and Norwich who were trained to deliver the intervention but were not able to deliver it within the study time frame. Results: The analysis identified five themes: (1) Acceptability, (2) Adherence, (3) Outcomes, (4) Feasibility and (5) Stand-alone themes (prehabilitation, video consultations, healthcare use). Patient-participants and physiotherapist-participants agreed that usual care was not meeting patients' rehabilitation needs. The GRRAND intervention provided biopsychosocial support. In comparison to the usual care group, patient-participants who received the intervention were more confident that they could perform rehabilitation exercises and were more motivated to engage in long-term adaptive behaviour change. Physiotherapists felt they needed more administrative support to participate in an RCT. Conclusion: Participants felt that usual care was insufficient. GRRAND provided much needed, biopsychosocial support to patients. Participants were supportive that it would be feasible to test GRRAND in an RCT. Trial registration number: ISRCTN11979997 .